The unsteady boundary layer flow past a circular cylinder in micropolar fluids - Ali, Anati (Emerald Group Publishing, 2007)
Purpose – The purpose of this paper is to study the unsteady boundary layer flow of a micropolar fluid past a circular cylinder which is started impulsively from rest.